Aktivitas Antioksidan Dan Total Fenol Seduhan Teh Herbal Daun Pacar Air (Impatiens balsamina L.) Dengan Variasi Metode Pengeringan Dan Konsentrasi - Indarwati, Dewi; , Dr. Nanik Suhartatik, S.TP., M.P (2015)
Tea is a drink that is very familiar in everyday life. The material produced can from pacar air leaves, pacar ai r leaves containing flavonoids, steroid, saponins, quinone, coumarin and antibacterial. The purpose of this study was to know antioxidant activity and total phenol steeping herbal tea leaf pacar air determine the appropriate concentration ofthe leaves to get the antioxidant activity and total phenol. The methods design was completely randomized design with two factors: factor 1 : drying method (oven 60oC (M1), direct sunlight (M2) and roasted (M3)) and factor 2:concentration (concentration 0,5% (K1), concentration 1% (K2) and concentration 1,5% (K3)) with 3 replications. The result of the research show that the variation method of drying and concentration affect the antioxidant activity of leaves and total phenols. Antioxidant activity and total phenol highest steeping herbal tea with roasted drying method and the concentration of leaves dried pacar air 1.5% is 83.57% and 10.28 mg as.galat 100 mL.